2010
DOI: 10.1159/000317845
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Warming of the Abdomen and of Herbal Medicine on Superior Mesenteric Artery Blood Flow – a Pilot Study

Abstract: Background: In traditional Japanese and Chinese medicine, warming the abdomen with moxibustion or herbal medicines has been used for various diseases. However, the effects of these therapies on hemodynamics have not been clear. We clarify the physiological effects of these therapies on the superior mesenteric artery (SMA) blood flow. Participants and Methods: 28 healthy male volunteers were randomly assigned to groups A and B. Group A (n = 14) underwent local thermal stimulation of the paraumbilical region for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…It has been reported that treating acupoint ST25, located on both sides of the umbilicus, with moxibustion helps the intestines become active and improves their function (Tabosa et al, 2004). We have successfully proved that heating the umbilicus increases the volume of blood flow in the superior mesenteric artery by using a heat conduction treatment device that we developed (Takayama et al, 2010Seki et al, 2011). Heating the affected area with moxibustion can remedy the condition of acute lymphangitis.…”
Section: Scientific Research On Moxibustion Treatmentmentioning
confidence: 92%
“…It has been reported that treating acupoint ST25, located on both sides of the umbilicus, with moxibustion helps the intestines become active and improves their function (Tabosa et al, 2004). We have successfully proved that heating the umbilicus increases the volume of blood flow in the superior mesenteric artery by using a heat conduction treatment device that we developed (Takayama et al, 2010Seki et al, 2011). Heating the affected area with moxibustion can remedy the condition of acute lymphangitis.…”
Section: Scientific Research On Moxibustion Treatmentmentioning
confidence: 92%
“…Furthermore, it was shown using ultrasound diagnostic equipment that local thermal stimulation, oral administration of Daikenchu-to, and acupuncture stimulation of ST36 change blood flow in the superior mesenteric artery (SMA) to a similar extent (Table 4) [16,20].…”
Section: Author's Conclusionmentioning
confidence: 99%
“…Acupuncture stimulation of ST36, HTCD treatment of the paraumbilical region, and the herbal medicine Dai-kenchu-to are different approaches, but all of them increase blood flow volume in SMA (Table 6) [16,20]. Herbal medicine Banxia Houpo Tang, acupuncture, and TES on ST36 and KI3 improve LTSR and may prevent aspiration pneumonia [8,12,36].…”
Section: Conclusion and Implications For Future Researchmentioning
confidence: 99%
“…Horiuchi et al reported that DKT significantly improved abdominal bloating and pain and reduced intestinal gas volume in patients with intractable functional constipation [8]. Physiological reactions to the administration of DKT have been reported as promoting gastrointestinal motility [913] and increasing intestinal blood perfusion [1419]. DKT's effectiveness in treating defecation disorders in patients with cerebrovascular disease is commonly observed in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…DKT has been used to treat defecation disorders with abdominal coldness and pain caused by decreased intestinal motility and blood flow. We previously reported that administration of DKT increased blood flow in the superior mesenteric artery and promoted intestinal peristalsis in healthy subjects [18, 19]. Sato et al reported that DKT significantly increased plasma CGRP levels in healthy subjects [21].…”
Section: Introductionmentioning
confidence: 99%